Study Antropometri Indeks Nasalis Suku Jawa, Batak Dan Melayu Pada Mahasiswa FK UISU Kota Medan 2021 - wan ismail (LPPM STIKes Indah Medan, 2021)
ABSTRACT Facial anthropometry is known as the science of measuring and analyzing the proportions of the human face and provides important information about differences in shape and size of various races, ages, and sexes. The size, shape and position of the nose determine the aesthetic appearance of the face and are important in prognosis. care, references to diagnostic, clinical, and forensic procedures. The general objective of this study was to obtain data on various forms of nasal indices in Javanese, Batak, Malay ethnic groups. This research is a descriptive study with a cross sectional approach. Data collection uses primary data by measuring. Samples were taken using purposive sampling method. The research sample is 75 people, each ethnic group is 25 people. Based on the nasalis lepthorhine index, the highest percentage was in the Javanese, 60% Mesorhine, the highest was the Malay, 41.4%, and the platyrrhine category was the largest, the Javanese and Batak, 34.3%, respectively, hyperchamarine, 33.3%, respectively, in the Javanese, Malay and Batak. Variations in the nasalis index prove that there is a possible gene pool that provides variation in the population. The gene pool of a particular population can change over time through the process of evolution. This can occur due to a variety of mechanisms, including mutation, natural selection, and genetic drift.